Monitoring forest biodiversity and the impact of climate on forest environment using high-resolution satellite images. Issue 1 (1st January 2018) - Bochenek, Zbigniew; Ziolkowski, Dariusz; Bartold, Maciej; Orlowska, Karolina; Ochtyra, Adrian
ABSTRACT: The main objectives of the research work were to determine the usefulness of Landsat and SPOT data for monitoring various forest parameters, and to assess the impact of changeable climatic conditions with the use of vegetation indices derived from remotely sensed data. Vegetation indices describing various aspects of plant condition and vegetation structure were derived from satellite images, and their values were analysed in a temporal profile in different vegetation seasons, in conjunction with meteorological parameters. The results of analyses proved that dedicated vegetation indices of water stress in plants – the disease water stress index (DSWI) and normalized difference infrared index (NDII) – are able to detect changeable climatic conditions, especially the impact of drought on forest ecosystems. The indices are also useful for characterising types of forest site and tree stand mixture, in particular differentiating dry, fresh and humid forest sites. Results of analysis of satellite-based indices were supported by conclusions drawn from a study of vegetation parameters obtained in the course of field campaigns.